PENGARUH PRIVATE BRAND TERHADAP SHOPPING PREFERENCE MELALUI BRAND EQUITY PADA PRODUK CARREFOUR DI SURABAYA - Andreani, Janesia (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
This study analyzes the various factors that affect the Shopping Preference on Carrefour private brand product. The purpose of this study was to determine the effect of variable Private Brand, Brand Equity and Shopping Preferences on Carrefour private brand products in Surabaya. The sampling technique used was purposive sampling, the sampling technique by using judgment based on certain criteria. The criteria used are: living in Surabaya, at least 17 years old and ever buy a Carrefour private brand product. The method used in this research is a method of Structural Equation Modeling (SEM) with LISREL 8.70 program. The research concludes that there is a strong influence and a significant positive relationship between the variables in each Private Brand, Brand Equity and Shopping Preference either directly or indirectly. The conclusion of the research is that consumers will buy Private Brand product if the product is to be trust and also has a wide range of factors - factors that need to be considered good and no more advantage.